Evaporation from carbon nanotube forest analytical possibilities of the mass measurements - Tóth Ildikó Y.; Sütő I.; Kukovecz Ákos; International Symposium on Analytical and Environmental Problems (26.) (2020) (Szeged) (2020)
The evaporation of liquids from porous materials is a very complex phenomenon, which can be followed by simultaneous weight monitoring, electric resistance measurement, infrared imaging and contact angel measurement. The appropriate evaluation of these measurement results can carry both quantitative and qualitative analytical information. The aim of our recent work is to demonstrate this opportunity through the example of the evaporation of simple solvents from a carbon nanotube forest. In this work the focus will be on the analytical possibilities of the mass measurements.
Keywords: Természettudományok; Kémiai tudományok